Relationship between sodium, calcium, and preeclampsia during pregnancy : a Cross-sectional study - Fitri Handayani; Fatimah Fatimah; Yulinda Kurniasari; Lia Dian Ayuningrum (Alma Ata University Press, 2019)
ABSTRACTBackground: In the world maternal mortality as many as 830 women died due to complications in childbirth. In 2015, 303.000 women died during pregnancy and after pregnancy. Target Sustainable Development Goals (SDGs) year 2030 lowers MATERNAL MORTALITY RATE under 70 per 100.000 live births. Pregnancy complications can cause bleeding before or after childbirth, preeclampsia, eclampsia, infections, and others. Maternal death case in Kab. Bantul in 2015 is 9 cases. Research Data in the Panembahan Senopati Hospital in the year 2017 the incidence of childbirth with complications of 1068 people. The prevalence of preeclampsia in expectant mothers is 176 people by 16.47%.Objectives: This research aims to know the relationship of sodium and calcium consumption in the mother of Nifas with preeclampsia during pregnancy in the Panembahan Senopati Hospital. Number of Samples were 54 postpartum women in Panembahan Senopati Bantul. Processing and analysis of data using the Chi-square test.Methods: This type of research is an analytical observational, with a research design using a cross-sectional.Results: Characteristics of most respondents in the age category of 20-35 years as many as 38 people (70.4%), education graduated of senior high school 28 people (51.9%), history of not hypertension as many as 51 people (94.4%) and has no preeclampsia history as much as 50 people (92.6%). Statistical test results of Chi-square and p-value sodium was 0.564 (> 0.05) and P-value calcium was 1.000 (> 0.05).Conclusion: There is no relationship between sodium and calcium consumption of postpartum women with preeclampsia problem during pregnancy at Panembahan Senopati Hospital.KEYWORDS: calcium, preeclampsia, sodium